Designing Roadside Noise Barrier - Jason Obadiah (Universitas Multimedia Nusantara, 2017)
Noise is the common problem in the residential area, whether it came from events, vehicles, construction sites, or urban area. The most affected residential area are usually the ones which adjacent to the highway or a road. When someone is overexposed from the noise, this could lead into many health problems. This is why a noise barrier is essential to be built along the road. problems regarding the noise barrier is that although the barrier can attenuates the noise from the traffic, there are other sound source, or in this case, noise source other than the traffic such as the airplane. This problem mostly happened on the residential ground around an airport. One of the solutions for these problems is by using vegetation as additional noise barriers. By doubling the barrier (noise barrier - vegetation) the attenuations will probably much higher, in accounts that the vegetation is much higher than the barrier so that if there are multiple floor buildings, the floors above will also provide with noise insulations. Although, it would be more appropriate to use acoustic treatments to the buildings. The other solution is that by using the concept of constructing a louver or cap atop the wall that is directed back toward the noise source. This concept follows the theory that such a design should inhibit shadow zone diffraction filling in sound behind the noise barrier. Keywords: noise, sound, barrier, attenuation